Redescriptions of three species of freshwater crabs from the Democratic Republic of Congo, Central Africa (Brachyura: Potamoidea: Potamonautidae) - Cumberlidge, Neil (Zootaxa, 2015)
The taxonomy of three species of freshwater crabs from the Upper Congo River in the Democratic Republic of Congo, Potamonautes congoensis (Rathbun, 1921), P. langi (Rathbun, 1921), and P. stanleyensis (Rathbun, 1921), is revised based on examination of the holotypes. Updated diagnoses, illustrations, and distribution maps are provided for these species, and their conservation status is discussed.